Migración interna y tamaño de localidad en México - Sobrino, Jaime (El Colegio de México A.C., 2014)
Rural-urban migration involves rising spatial mobility, since the place of origin has a smaller population than the place of destination. In Mexico, at least since 2000, urban-urban migration has been the prevailing flow in internal migration, comprising spatial mobility that is ascendant and descendant, or from places with a greater to smaller population size. This article aims to analyze migratory flows by size of town during the periods from 1995 to 2000 and from 2005 to 2010, to show the spatial and economic-productive characteristics of the places of origin and destination, and the migrants’ socio-demographic attributes in terms of gender, age, educational attainment and perceived income. The results allow to establish the importance of the population size of the places of origin and destination in population mobility. This situation fosters differentiated flows based on the distance covered, local economic structure and the migrants’ socio-demographic characteristics. The article reveals a greater dynamism in the volume ofdescendant spatial mobility, and more adverse conditions for integration into the labormarket among persons with ascendant spatial mobility.